2017
DOI: 10.5155/eurjchem.8.2.149-154.1563
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of some novel N-substituted benzimidazoles

Abstract: Synthesis of a series of new substituted benzimidazole derivatives by the condensation of o-phenylenediamine with urea to give 1,3-dihydro-benzimidazol-2-one which reacted with phosphoryl chloride to give 2-chloro-1H-benzimidazole is reported. The product was then alkylated at the benzimidazole NH with different electrophilic reagents leading to functionalized derivatives. Structures of the newly synthesized products have been deduced on the basis of spectral and analytical data. The synthesized compounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Indeed, the optimization of the biological properties depends on the nature of the substituents on these positions [12] [13]. Recent studies showed that presence of a thiol group in 2 position enhanced biological activities such as antimicrobial [14], inflammatory [15], antiviral [16], antibacterial [17], antioxidant [18] [19], anticancer [20] and anti-proliferative [21]. It should be noted that, despite the large therapeutic arsenal, there is still an efficiency limit effects proved by the increase in strains resistant to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the optimization of the biological properties depends on the nature of the substituents on these positions [12] [13]. Recent studies showed that presence of a thiol group in 2 position enhanced biological activities such as antimicrobial [14], inflammatory [15], antiviral [16], antibacterial [17], antioxidant [18] [19], anticancer [20] and anti-proliferative [21]. It should be noted that, despite the large therapeutic arsenal, there is still an efficiency limit effects proved by the increase in strains resistant to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental Data: For the generation of QSAR models, firstly, 32 benzimidazole analogues were selected from various reported literature for studying their antibacterial activity 10,11,12 . Further for the 2D-QSAR model development, the pMIC values were calculated as Log (1/MIC), where the literature reported MIC values were first converted into μM/mL.…”
Section: Materials and Methods: The Complete Computerizedmentioning
confidence: 99%
“…As part of our ongoing research, we were interested in designing N -substituted benzimidazoles which were presented in many biologically active compounds. 24,27 Our designed derivatives and Dovitinib anticancer drug, Benomyl antifungal drug, and antibacterial derivatives of Dokla et al , 2020 (MIC on E. coli strain of 2 μg mL −1 ) share three common essential structural features: a planar benzimidazole moiety, C-2 aromatic substitution, and N-1 substitution. 28 Moreover, the C-6 position with different substituents such as –H and –CH 3 were designed in order to examine their effects on antimicrobial and anticancer activities (Fig.…”
Section: Introductionmentioning
confidence: 99%